Age and disease-related structural changes in the retinal pigment epithelium - Vera L Bonilha (Dove Medical Press, 2008)
Vera L BonilhaCole Eye Institute, The Cleveland Clinic, Cleveland, OH, USAAbstract: As the retinal pigment epithelium (RPE) ages, a number of structural changes occur, including loss of melanin granules, increase in the density of residual bodies, accumulation of lipofuscin, accumulation of basal deposits on or within Bruch’s membrane, formation of drusen (between the basal lamina of the RPE and the inner collagenous layer of Bruch’s membrane), thickening of Bruch’s membrane, microvilli atrophy and disorganization of the basal infoldings. Although these changes are well known, the basic mechanisms involved in them are frequently poorly understood. These age-related changes progress slowly and vary in severity in different individuals. These changes are also found in age-related macular degeneration (AMD), a late onset disease that severely impacts the RPE, but they are much more pronounced than during normal aging. However, the changes in AMD lead to severe loss of vision. Given the many supporting functions which the RPE serves for the retina, it is important to decipher the age-related changes in this epithelium in order to understand age-related changes in vision.Keywords: retinal pigment epithelium, aging, age-related macular degeneration (AMD), ocular disorders, retinal disease